Communication and mobilization campaigns for immunization (CMCI): need of time for strengthening Immunization services in India - Debaje, Samadhan Prakashrao (International Journal of Research in Medical Sciences, 2017)
After 65 years of independence India’s growth in health sector is remarkable which is result of flexibility in changes in strategies for achieving goal .Still there is not so well organized and recognizable growth in field of routine immunization. There is not much progress in strategies for communication and social mobilization; communication strategies always was major component in changing behavior of community and change in communities vaccine acceptance which help in preventing disease by improving immunization coverage. Many studies did so far indicate barriers for immunization as fear of AEFI, lack of knowledge of immunization, its benefits and information regarding where to get vaccination. These all barriers can be combined under one roof as communication and social mobilization barriers. When India had launched polio eradication program it had faced same difficulties due to cultural and social differences in India. As there were many regions where refusal and acceptance of vaccine with less coverage over booth observed, so India had revised its strategies of communication and social mobilization and implemented house to house activity through strategic approach to families with refusal and improved acceptance of polio vaccine through communication by house to house visits thus targeted intervention for improving communication and social mobilization for polio eradication initiative. India had achieved polio eradication mainly through revising its strategies for communication and mobilization. So there is urgent need for revising communication and mobilization strategies for strengthening immunization services in India. As India had shown its success through targeted intervention in strategies and we can use current polio work force available for strengthening routine immunization. As done in polio campaign we can use the targeted house to house activity strategy for identifying and planning for identified gaps in communication and mobilization for immunization. This Communication and Mobilization Campaign for Immunization (CMCI) can be planned for states with low percentage of full immunization coverage based on health survey as NHFS or AHS.